Revisiting Dynamic Convolution via Matrix Decomposition - Li, Yunsheng; Chen, Yinpeng; Dai, Xiyang; liu, mengchen; Chen, Dong; Yu, Ye; Yuan, Lu; Liu, Zicheng; Chen, Mei; Vasconcelos, Nuno (2021 International Conference on Learning Representations, 2021)
Recent research in dynamic convolution shows substantial performance boost for efficient CNNs, due to the adaptive aggregation of K static convolution kernels.It has two limitations: (a) it increases the number of convolutional weights by K-times, and (b) the joint optimization of dynamic attention and static convolution kernels is challenging. In this paper, we revisit it from a new perspective of matrix decomposition and reveal the key issue is that dynamic convolution applies dynamic attentions over channel groups after projecting into a higher dimensional intermediate space. To address this issue, we propose dynamic channel fusion to replace dynamic attentions over channel groups. Dynamic channel fusion not only enables significant dimension reduction of the intermediate space, but also mitigates the joint optimization difficulty. As a result, our method is easier to train and requires significantly fewer parameters without sacrificing accuracy.